2013
DOI: 10.1111/bph.12280
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine‐site pharmacology on GABAA receptors in histaminergic neurons

Abstract: BACKGROUND AND PURPOSEThe histaminergic tuberomamillary nucleus (TMN) of the posterior hypothalamus controls the cognitive aspects of vigilance which is reduced by common sedatives and anxiolytics. The receptors targeted by these drugs in histaminergic neurons are unknown. TMN neurons express nine different subunits of the GABAA receptor (GABAAR) with three α-(α1, α2 and α5) and two γ-(γ1, γ 2) subunits, which confer different pharmacologies of the benzodiazepine-binding site. EXPERIMENTAL APPROACHWe investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The GABAergic synapses formed on histaminergic TMN neurons express at least nine different GABA A receptor subunits: α1, α2, α5, β1, β2, β3, γ1, γ2, and ε [46] . Although the γ1-subunit of GABA A receptors likely contributes to the action of common sedatives in TMN neurons [17] , Wafford et al reported that the α1β1γ2 GABA A receptor subunit combination, which forms a type-1 benzodiazepine receptor, allowed ethanol enhancement of GABA responses, whereas other GABA A receptor subunit combinations did not, even at high ethanol concentrations [47] . Hence, the specific GABA A receptor subtype responsible for the effect of ethanol in the TMN remains to be examined in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GABAergic synapses formed on histaminergic TMN neurons express at least nine different GABA A receptor subunits: α1, α2, α5, β1, β2, β3, γ1, γ2, and ε [46] . Although the γ1-subunit of GABA A receptors likely contributes to the action of common sedatives in TMN neurons [17] , Wafford et al reported that the α1β1γ2 GABA A receptor subunit combination, which forms a type-1 benzodiazepine receptor, allowed ethanol enhancement of GABA responses, whereas other GABA A receptor subunit combinations did not, even at high ethanol concentrations [47] . Hence, the specific GABA A receptor subtype responsible for the effect of ethanol in the TMN remains to be examined in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether ethanol affects the activity of histaminergic neurons in the TMN remained unknown. Given that GABA A and GABA B receptors are present in GABAergic synapses on histaminergic TMN neurons [16,17] , we hypothesized that ethanol may alter GAB-Aergic transmission in the TMN.…”
Section: Original Articlementioning
confidence: 99%
“…Like many benzodiazepines, zolpidem exhibits sedative and hypnotic effects via α1 containing receptors, but unlike benzodiazepines, zolpidem reverses cognitive and motor deficits in neuropathological states, improves motor function in patients with Parkinson’s disease, progressive supranuclear palsy and stroke 13 14 15 16 17 . Studies also show that there are residual effects with zolpidem in the γ2 F77I mouse where binding by zolpidem to α(+)-γ2(−) is attenuated 18 19 . Further, zolpidem can modulate tonic GABA currents in the rat dorsal motor nucleus of the vagus 20 and primary motor cortex 15 , implicating extrasynaptic receptors containing α5 and δ subunits.…”
mentioning
confidence: 99%
“…As well as removing zolpidem sensitivity, the γ2F77I point mutation results in DMCM insensitivity (Buhr et al, 1997; Ogris et al, 2004; Leppä et al, 2005). Nevertheless, DMCM will act as an inverse agonist at γ3 subunit-containing GABA A Rs (Herb et al, 1992; Kerti-Szigeti et al, 2014), while DMCM will potentiate γ1-containing GABA A Rs (Puia et al, 1991; Khom et al, 2006; May et al, 2013). In control cells, 10 μM DMCM significantly enhanced the average sIPSC charge transfer by 39.8 ± 15.59% ( n = 7) due to a combined action on the peak amplitude and decay of sIPSCs (paired t -test, P = 0.004; Figure 4D).…”
Section: Resultsmentioning
confidence: 99%